Pola Pendidikan Maritim dalam Membentuk Jiwa Kewirausahaan Mahasiswa di Politeknik Maritim Negeri Indonesia - Endra Winarni (Jurnal Maritim Polimarin, 2018)
The initial thinking that underlies this research is that the most recent data from the Global Entrepreneurship Monitor (GEM) shows that Indonesia has only around 1.65 percent of entrepreneurs of a total population of 252 million. Indonesia has enormous potential and opportunities to obtain economic resources from maritime. The maritime entrepreneurship program is not only to open up new hopes for the society but also as an effort to encourage private sector to play a role in building Indonesia's maritime affairs. The spirit of entrepreneurship must be cultivated in student's mind as a reference for the success of universities in building intelligent people. The purpose of this article is to explore and to try for gaining the insight about the pattern of maritime education in shaping the entrepreneurial spirit of students conducted at Politeknik Maritim Negeri Indonesia. Problems formulated: 1) What is the description of the spirit of entrepreneurship possessed by Polimarin students, 2) How is the design of an entrepreneurship education program involving internal and external parties in order to create a generation of educated entrepreneurship in Polimarin. The method used in this research is in-depth interviews with alumni as an entrepreneur, business simulations and focused group discussions with active students, as well as literature studies by reviewing books and journals. The results of the discussion stated that: The tone of Polimarin student entrepreneurship education is carried out through practical learning with experiential based learning methods. The growth of entrepreneurial spirit through practical learning by conducting business practices include: practical activities in setting up small-scale bazaars, price research practices in the market, creating brand (brand), practice simulation of business stages such as sevron turnover by means of student sewing services because students live in dormitories, the practice of selling merchandise, the practice of producing goods with existing natural resources, the practice of optimizing existing capital for production, seeking technology to make production more efficient.